Electronic transport properties of indium antimonide nanowire clusters synthesized by electrodeposition method - Arifin @ Mohd Ripin, Intan Nur Ain (2019)
Indium antimonide (InSb) is a promising semiconducting material that has been implemented in various electronic applications due to its high carrier mobility and carrier density. In particular, studies of InSb nanowire clusters have yet to be explored in detail, despite the advantages of wire clusters can bring to the to the touch screen technologies and flexible devices. Therefore, the main focus of this thesis is to study the electronic transport properties within InSb nanowire clusters such as schottky barrier height (SBH), conductivity, carrier density, and carrier mobility. According to field emission scanning electron microscope-energy dispersive x-ray (FESEM-EDX) analysis, the clusters comprised of agglomerated, flowery-shaped nanowires and bulk InSb, with stoichiometric 1:1 ratio. The x-ray diffraction (XRD) analysis shows that the wire clusters exhibit polycrystalline nature, with several impurities present such as Sb, In2O3, Sb2O3, and Al2O3. In order to study the electrical transport behaviours of InSb nanowire clusters, two parameters, namely nanowire diameters and contact gap widths were chosen. For the effects of nanowire diameters, it was observed that most electronic transport properties such as conductivity (0.34 to 3.61 × 10-4 S/m), carrier density (7.41 to 7.49 × 1010 cm-3), and carrier mobility (0.48 to 4.82 × 10-15 cm2 V-1 s-1) increases with increasing diameters (20 to 200 nm). This is due to several reasons such as decreased grain boundaries and scattering effects, as well as increased electron charge density, thus allowing easier movement of carriers throughout the metalsemiconductor- metal (MSM) junction. Meanwhile, SBH is shown to be inconsistent with increasing diameter, which is possibly because of the presence of InSb bulk structure that might have influenced the electronic transport within the wire clusters. For the effects of contact gap width, most of the electronic transport properties such as conductivity (1.67 to 4.58 × 10-5 S/m), carrier density (7.41 to 7.45 × 1010 cm-3), and carrier mobility (0.23 to 0.61 × 10-15 cm2 V-1 s-1) were shown to increase with decreasing gap size (343.07 to 277.72 μm), while SBH decreases (0.68 to 0.66 eV). This is because of the closer distribution within nanowire clusters when the gap width decreases, and hence improving the current transport throughout the MSM junction. Due to several factors such as presence of defects and less compact distribution compared to particle arrangements within bulk structure, thin film and single nanowire, nanowire clusters exhibit lower electronic transport properties. Nevertheless, further investigations on the semiconductor nanowire clusters will open more opportunities to discover its potentials in a wide variety of electronic components in the future.